Water policy interventions for food security in Afghanistan. Issue 1 (2nd January 2019) - Acquah, Sarah; Ward, Frank A.
Abstract: Afghanistan is a headwater state that contributes supplies to several countries in Central and South Asia. However, despite being a water source, it faces the challenge of establishing its own storage infrastructure and water-sharing methods to protect its food security. This article investigates impacts on the Afghan agricultural sector resulting from enhanced reservoir storage capacity and better-performing water-sharing methods. An integrated systems analysis is formulated to analyze the economic performance of both interventions. Results reveal that both interventions show the highest capacity to improve food security in conditions where water supply shows the greatest natural fluctuations.